Primary cutaneous anaplastic large cell lymphomas with 6p25.3 rearrangement exhibit particular histological features. Issue 6 (4th February 2015) - Onaindia, Arantza; Montes‐Moreno, Santiago; Rodríguez‐Pinilla, Socorro M; Batlle, Ana; González de Villambrosía, Sonia; Rodríguez, Antonio M; Alegre, Víctor; Bermúdez, Glenda M; González‐Vela, Carmen; Piris, Miguel A
<x xml:space="preserve">Abstract</x> Aims CD30‐positive primary cutaneous lymphoproliferative disorders include several entities with differing clinical presentation but overlapping histological features, including lymphomatoid papulosis and primary cutaneous anaplastic large cell lymphoma (C‐ALCL). DUSP22–IRF4 locus translocation is present in 20–57% of C‐ALCLs, and has also been described in a series of 11 lymphomatoid papulosis patients, where it was associated with a particular biphasic histological pattern, including pagetoid reticulosis‐type epidermal infiltration. We aimed to study whether the presence of this translocation may define distinctive histological features in C‐ALCL. Methods and results We collected three cases of C‐ALCL with histological features similar to those described in the new variant of lymphomatoid papulosis with 6p25.3 rearrangement. We studied their histological features and immunophenotype, using a panel of antibodies against CD30, TCR‐βF1, TCR‐γ, CD4, CD8, CD20, Ki‐67 and ALK. FISH analyses were performed using an IRF4–DUSP22 break‐apart probe for the study of the 6p25.3 rearrangement. FISH results were positive in the three cases, which all showed distinctive histological and immunohistochemical features: a diffuse dermal infiltrate of atypical medium‐to‐large cells, and marked epidermotrophism with small, atypical intra‐epidermal lymphocytes. Conclusions Our findings suggest that the presence of 6p25.3 rearrangement might be related to this particular biphasic pattern.